Transformation of Principal Leadership in The 5.0 Era - Dinda Syahfitri (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
The leadership of school principals plays a crucial role in the success of educational organizations, especially in facing the Society 5.0 era that integrates technological advancements with human values. Leadership transformation in this era demands school principals to become adaptive, visionary, and innovative change agents, capable of leveraging digital technology and developing an inclusive and collaborative school culture. This literature review identifies four main trends in the transformation of school leadership, namely the strengthening of digital leadership, the development of collaborative leadership, the integration of spiritual values, and the need for a contextual adaptive leadership model. The study results affirm that continuous professional development and policy support are key to the success of school principals in leading sustainable and relevant educational transformations in response to contemporary challenges. This transformation is not just an administrative change, but rather a holistic and humanistic paradigm shift in creating an adaptive and competitive education system.